Logit Model for Prediction of Financial Health in Automotive Industry - Kronová, Jana; Peter Trebuňa; Miriam Pekarčíková; Milan Fiľo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
This article aims to evaluate the financial health of companies operating in the automotive industry in the Slovak Republic and to predict impending bankruptcy using a selected mathematical-statistical method. The research sample consisted of 351 companies from the automotive industry. The basis for the creation of the prediction model is the financial indicators from the previous accounting period. The most significant indicators were selected using LASSO regression. The mathematical-statistical logit method was used to create the model. The success rate of the resulting logit model is assumed to be 78% in predicting the possible bankruptcy of companies in the automotive industry.